Analisis Pengaruh Tangible, Reliability, Responsiveness, Assurance dan Empathy terhadap Kepuasan Pasien Rawat Jalan di Rumah Sakit Umum Daerah Pambalah Batung Kabupaten Hulu Sungai Utara - Azhar, Khairullah; Ruspitasari, Widi; Bukhori, Moh (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
Service quality is the best service provided by individuals, groups or organizations that give satisfaction to society. At the reception of outpatients at Pambalah Batung Hospital, Hulu Sungai Utara District, there are several problems, namely waiting time. The patient registration process is relatively slow due to limited resources (service officers) on duty at the Outpatient Patient Registration Site (TPPRJ). ) service staff on duty and limited information facilities related to service mechanisms and conditions that must be met by patients and The purpose of this study was to analyze the effect of Tangible, Reliability, Responsiveness, Assurance and Empathy on Outpatient Patient Satisfaction at the Pambalah Batung District General Hospital Upper North River. This research was conducted at Pambalah Batung Hospital, Hulu Sungai Utara District. The sample used was 58 respondents. The independent variables in this study are Tangible, Reliability, Responsiveness, Assurance and Empathy, while the dependent variable is Outpatient Satisfaction. Data analysis was performed using the Structural Equation Model (SEM) method. The software used for structural analysis is Smart PLS V.4. From the test results using the Smart PLS Version 4 application, it can be concluded that the Direct Evidence and Reliability Variables have a significant and positive effect on outpatient satisfaction while the Responsiveness, Assurance and Empathy Variables have an insignificant but positive effect further based on the Adjusted R-Squared value of 0.937 or 93.7%, the remaining 6.3% are other factors that also affect patient satisfaction, including errors.